Lexicographical Features of the Kawkabān Fatḥ al-Qarīb Dictionary: Microstructure, Macrostructure, and Pedagogical Implications - Ilvi Tamarisa Syarova; Sofyan Sauri; Yusuf Ali Tantowi (Jurnal Internasional Pendidikan Bahasa Arab, 2026)
Dictionaries play a critical role in Arabic language learning, particularly in supporting reading comprehension of classical Islamic texts. However, thematic dictionaries integrated into specific teaching methods, such as the Kawkabān Fatḥ al-Qarīb dictionary used in the Tamyiz Method, remain largely unexamined from a lexicographical standpoint. This study analyzes the microstructural and macrostructural features of the Kawkabān Fatḥ al-Qarīb dictionary and their pedagogical implications within the Tamyiz Method, using Zgusta's lexicographical framework. Data were drawn from 56 entries selected through stratified purposive sampling across nine letters of the Arabic alphabet and analyzed using content analysis with five coding indicators: meaning, lemma consistency, grammatical information, usage examples, and semantic relations. The findings reveal that all entries consistently present basic meanings and lemma consistency (100%), while grammatical information, usage examples, and semantic relations are entirely absent (0%). Macrostructurally, the dictionary employs a hybrid alphabetical and root-based arrangement coherent with the method's pedagogical progression. This study contributes to Arabic pedagogical lexicography by demonstrating that the dictionary's structural limitations reflect a deliberate functional orientation rather than lexicographical deficiency. Future thematic dictionaries should incorporate grammatical categories and semantic relations to support deeper and more transferable vocabulary acquisition.